Tao rin ako experiencing the trauma of being queer in a postcolonial Filipino society - Reyes, Asaliah Reiiel B.
Tao Rin Ako is an attempt to externalize and express my queer trauma from bullying by creating a textile sculpture, along with specifically selected objects in an installation piece that leans heavily on Ellen DeLara's Adult Post-Bullying Syndrome and Jennier Ratcliff et. al., Posttraumatic Growth Posttraumatic Depreciation as a guide.